2013
DOI: 10.7224/1537-2073.2012-032
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Quality of Life and Related Psychosocial Variables in Australians with Multiple Sclerosis

Abstract: This study explored changes in quality of life (QOL) and psychosocial variables in a large cohort of people with multiple sclerosis (MS). A total of 1287 Australians with MS were administered self-report questionnaires at baseline and 24 months later to examine the impact of disease severity and duration, perceived stress, self-efficacy, depression, and social support on QOL and self-care. Over the 2-year survey period, MS remained stable for 70% of respondents. Disease severity correlated with social support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Consistent with previous research, demographic and physical disability were not predictive of PCI. 44,45 Taken together, results suggest that individuals' perceptions of their abilities to manage their symptoms predict the presence and severity of perceived cognitive impairment, which has important implications for predicting positive health outcomes (e.g., community integration) and for designing successful self-management interventions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Consistent with previous research, demographic and physical disability were not predictive of PCI. 44,45 Taken together, results suggest that individuals' perceptions of their abilities to manage their symptoms predict the presence and severity of perceived cognitive impairment, which has important implications for predicting positive health outcomes (e.g., community integration) and for designing successful self-management interventions.…”
Section: Discussionmentioning
confidence: 95%
“…It featured a longitudinal design with a large sample of community-dwelling individuals with MS. A review of the current literature revealed only two longitudinal studies of self-efficacy in MS, one as a predictor of health-related quality of life, 45 and the other on physical activity behaviors. 48 However, neither study explicitly investigated PCI.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Other psychological or person-specific factors include anxiety, self-efficacy, and coping. 36 Perceived social support has also been shown to be a significant factor associated with QOL in MS. 28 These factors have been shown to greatly contribute to QOL above and beyond disease variables. In fact, Wollin et al (2013) found that depression, anxiety, self-efficacy, social support, and stress accounted for an additional 40% of the variance in predicting QOL when disease severity and duration were accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Wollin et al (2013) found that depression, anxiety, self-efficacy, social support, and stress accounted for an additional 40% of the variance in predicting QOL when disease severity and duration were accounted for. 36 Self-efficacy has consistently been hailed as a great determinant in MS with regard to several outcomes, including health status, 37 adherence to treatment, 38 disease management, 39 adjustment, 40 physical and social functioning, 41 and physical activity and HRQOL. 42 A more recent investigation found self-efficacy to be a significant predictor of physical, social, and cognitive functioning in MS, even when taking into account neurologic impairment and depression.…”
Section: Introductionmentioning
confidence: 99%
“…age, gender) or clinical (duration of MS) variables that provide only limited explanatory power for the progression of functional limitations [9,10,11,12,13]. In a widely cited study conducted before the advent of disease-modifying medications, Weinshenker and colleagues found that 50% of persons with MS require the use of an assistive device for walking 15 years after diagnosis and 10% require a wheelchair to support mobility [14].…”
Section: Introductionmentioning
confidence: 99%